The interactive effects of societal and organizational cultural tightness on employee work related outcomes - ZHAO, Na (Institutional Knowledge at Singapore Management University, 2023)
Individuals are shaped by both their organizational and societal cultures, yet existing research often approaches these cultural dimensions in isolation, ignoring their combined impact on individual behaviors. In response to this research gap, I developed a novel theoretical framework by combining cultural tightness literature with social information processing theory. This framework highlights the interactive impacts of societal and organizational cultures on employees’ outcomes, including job performance, work attitudes, and mental health. Moreover, I proposed several mechanisms, including motivational, cognitive, and emotional mechanisms, through which these forms of cultural tightness could shape these specified work-related outcomes. To validate this framework, I have conducted two empirical investigations within the sociocultural context of China, providing a partial examination of the proposed theoretical model.